The storage battery - Foster, Louis Cloyd; Maus, Chester Arthur (My University, 1904)
Introduction: The first storage cell was invented in 1801 by M. Gautherot but not until 1881 was it used to any extent. There is record of the application of a storage battery in England in that year. The first battery installed in this country was at a central station in Phillipsburg, Pa., in 1885 while 1889 marks the beginning of the general application of the storage battery in the commercial world. The storage battery or accumulator consists of two inert plates of metal or some oxide of metal placed in an electrotype which is incapable of acting upon than chemically, until by the action of an electric current passed through the cell, the nature of the material on the plates is changed.
Citation: Foster, Louis Cloyd and Maus, Chester Arthur. The storage battery. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Battery; Practical Application; Electronics; History of Battery; Theses